Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1590/s0102-05362003000100023
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de plantas e produção de rizomas de taro 'Chinês' em função do tipo de muda

Abstract: O riginário da Ásia, o taro [Colocasia esculenta (L.) Schott], também conhecido como inhame no centro-Sul do Brasil, é uma planta monocotiledônea da família Araceae (Plucknett, 1983). A planta adulta é constituída de um rizoma central (rizoma mãe ou cabeça central), do qual são formados, lateralmente, vá-rios rebentos (rizomas filhos), órgãos, esses, de importância na exploração comercial. Dos rizomas, principalmente do rizoma mãe, saem longos pecíolos car-PUIATTI, M.; KATSUMOTO, R.; PEREIRA, F.H.F.; BARRELLA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Moreover, these authors found a yield of commercial rhizomes of 29.1 t ha -1 . Another study conducted with Japanese taro showed that N, P, and K exports by rhizomes were 193, 47.0, and 443 kg ha -1 , respectively, with a yield of 66.0 t ha -1 (Puiatti, Greeman, Katsumoto, & Favero, 1992). These findings indicate that the amounts of nutrients exported by arrowroot and taro rhizomes are high and similar, especially for K and N. The amount of Mg exported by arrowroot rhizomes was relatively high, especially for the variety Seta.…”
Section: Macronutrients In Storage Rhizomesmentioning
confidence: 82%
“…Moreover, these authors found a yield of commercial rhizomes of 29.1 t ha -1 . Another study conducted with Japanese taro showed that N, P, and K exports by rhizomes were 193, 47.0, and 443 kg ha -1 , respectively, with a yield of 66.0 t ha -1 (Puiatti, Greeman, Katsumoto, & Favero, 1992). These findings indicate that the amounts of nutrients exported by arrowroot and taro rhizomes are high and similar, especially for K and N. The amount of Mg exported by arrowroot rhizomes was relatively high, especially for the variety Seta.…”
Section: Macronutrients In Storage Rhizomesmentioning
confidence: 82%